Organization Theory and the Resource-Based View of the Firm: The Great Divide. (September 2021) - Davis, Gerald F.; DeWitt, Theodore
The resource-based view of the firm has become dominant within the field of strategic management, yet it has had surprisingly little influence within organization theory. In this article, we document the divide between strategy and organization theory and propose an interpretation. Choices of theories are largely driven by a researcher's dependent variables, and the questions "Why do firms do what they do?" and "Why do some firms perform better than others?" can have distinct answers. Thus, strategic management scholars and organization theorists are like howler monkeys and spider monkeys, coexisting peacefully in the same ecosystem by dining on different dependent variables. We further speculate on the looming existential crisis for both fields as traditional firms are increasingly unsustainable due to the transformation wrought by the digital revolution in product markets and the markets for capital, labor, and supplies.